Phytohormones as Growth Regulators During Abiotic Stress Tolerance in Plants - EL Sabagh, Ayman; Islam, Mohammad Sohidul; Hossain, Akbar; Iqbal, Muhammad Aamir; Mubeen, Muhammad; Waleed, Mirza; Reginato, Mariana; Battaglia, Martin; Ahmed, Sharif; Rehman, Abdul; Arif, Muhammad; Athar, Habib-Ur-Rehman; et al. (Frontiers in Agronomy, 2022)
Phytohormones (PHs) are important regulators of the plant life cycle under optimum and non-optimum conditions (characterized by different stresses). PHs have a critical role in the interaction of plants towards the environment, and they can offset the detrimental impacts that different stresses pose during plant growth and reproduction. Recently, various studies have highlighted the role of PHs such as abscisic acid, salicylic acid, ethylene, and jasmonates in the plant responses towards environmental stresses. The involvement of cytokinins, gibberellins, auxin, and relatively novel PHs such as strigolactones and brassinosteroids has been documented under normal and stressful plant growth and development. The recent identification of the first plant melatonin receptor opened the door to this regulatory molecule being considered a new plant hormone. However, polyamines, which are not considered PHs, have been included in this chapter. We propose these organic compounds as a new type of plant growth regulator to cope with environmental stresses. This chapter focused on the recent developments in the knowledge related to PHs and their involvement in abiotic stresses of anticipation, signaling, cross-talk, and activation of response mechanisms.